Perancangan Interior Magnum Kafe di Surabaya - Ongkohadi H, Yusuf (Intra, 2014)
Café is the place which perfect place to gather or just relaxation from tight activities. Café usually have light food and drink for dish and have live music for additional entertainment. Magnum café is ice cream café from Unilever Walls product which was openened in Jakarta city and Surabaya city not yet. In this café the visitor can also learn more about history of Walls from beginning until now. From this café also give different atmoshphere than another café like give something unic in every room which place to this café. And the hope is give something interesting to visitor who come to this café.